Influence of microbial polysaccharides on the formation of structure of protein-free and gluten-free flour-based products - Mykhaylov, Valerii; Samokhvalova, Olga; Kucheruk, Zinoviya; Kasabova, Kateryna; Simakova, Olga; Goriainova, Iuliia; Rogovaya, Alla; Choni, Inna (Eastern-European Journal of Enterprise Technologies, 2019)
The formation of a structure of certain dietary bakery products and flour confectionery products made without wheat flour is difficult due to the absence of gluten. There is a constant search for effective structure-forming agents to replace gluten proteins. We investigated an influence of microbial polysaccharides (MPS) of xanthan, enposan, and gellan on the formation of a structure of gluten-free and protein-free bread and gluten-free muffins in the study. The ability of a model protein-free system based on corn starch was studied to form dough with addition of xanthan, enposan, and gellan in the amount of 0.1...0.5 % by weight at Brabender farinograph. It was found that presence of the investigated microbial polysaccharides in the amount of 0.3...0.5 % enabled the formation of dough with indicators that ensured formation of the necessary structure of dough without gluten. We investigated an influence of MPS on resilient-elastic and plastic-viscous properties of gluten-free dough. It was found that reopex properties disappeared in protein-free dough due to addition of xanthan. Viscosity of protein-free dough with addition of 0.3...0.5 % of xanthan by the mass of starch reached the values, which are characteristic for wheat bread dough. The amount of MPS of 0.1 % by weight of finished products is sufficient in gluten-free confectionery dough for muffins. Effective viscosity increased by 2...3 times for all investigated MPS and provided the desired consistency of dough for formation by the sedimentation method in this case. We studied quality indicators of baked products with addition of the investigated MPS. It was shhown that their use in certain quantities leads to an increase in the specific volume and to ensuring of the porous structure of baked products. Crumbling of products decreased during storage, which indicated a slowdown of hardening processes in gluten-free systems with xanthan, enposan, and gellan. All studied MPS exhibited the same nature of influence on certain indicators, but xanthan had the greatest effect, and gellan ‒ the least one